DO FOREIGN OWNERSHIP, PROFITABILITY, AND LEVERAGE INFLUENCE TAX AVOIDANCE OF INDONESIAN MINING COMPANIES? - Fira Faradisa; Heru Fahlevi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study is aimed to examine the influence of foreign ownership, profitability, and leverage on tax avoidance practices. This study tested the hypotheses in mining companies listed on Indonesia Stock Exchange (IDX) from 2018 to 2020. Using purposive sampling technique, 39 out of 46 companies in the Indonesian mining industry were taken as a sample with a total of 117 data observations for the period pre and during the COVID-19 pandemic. The data was then analyzed comparatively through multiple linear regression analysis. The results of this study revealed that for the period pre-COVID-19 pandemic, all independent variables simultaneously affect the dependent variable. Partially, foreign ownership and leverage have no significant effect on tax avoidance. However, profitability has a negative effect on tax avoidance. In contrast, for the period during the COVID-19 pandemic, all independent variables simultaneously and partially did not affect the dependent variable.